Controlled Burning and its Effects on Shorea robusta (Sal) Regeneration in Dhansar Block Forest, Rautahat - Dhungana, Badri Prasad; Bhatta, Balram; Sharma, Sundar; Chhetri, Vivek Thapa (International Journal of Environment, 2023)
Fire is used as a management tool to administer a wide range of ecosystems worldwide. Forest fires in Shorea robusta (Sal-dominated) forests take the form of ground fires and mostly affect regeneration. We investigated the effect of forest fire on Sal regeneration in 42 sample plots, of which 21 were subjected to controlled burning. The results showed that species richness decreased from fire-unaffected (19) to fire-affected (10). The total density of Sal seedlings in the fire-affected sites was 3829 seedlings ha-1, while in the fire-unaffected sites were 1779 seedlings ha-1 representing an increased species dominance of Sal species in the post-fire condition. The total density of Sal saplings in the fire-affected sites was 343 seedlings ha-1, while in the fire-unaffected sites was 571 seedlings ha-1. A significant difference with a large effect size (Cohen’s d=0.97) was observed in the seedling regeneration of Sal, while no significant difference was observed in the sapling regeneration of Sal in the post-fire condition. The increment of Sal seedlings may be due to the fire-hardy silvicultural characteristics of Shorea robusta and the decline of Sal saplings may be due to stem mortality in the small diameter classes. We conclude that fire is a beneficial tool for seedling regeneration but not for plant establishment. Future research studies regarding the impact of fire intensities, soil moisture, biological disturbances, temperature, light intensity, etc. on regeneration are recommended.